Dampak Program Kampus Mengajar dalam Meningkatkan Kualitas Hasil Belajar Kelas 4 SDN 43 Kota Bengkulu - Efan tri ahsyar; Mardhiyah Dwi Ilhami; Furqonti Ranidiah (Yayasan Darussalam Bengkulu, 2024)
This research examines the impact of the Teaching Campus Program on improving the quality of learning outcomes for grade 4 students at SDN 43 Bengkulu City. This program is part of the government's initiative in the Independent Learning-Free Campus Policy, which aims to integrate tertiary students into the primary school system to increase teaching resources and enrich the learning process. This study uses a quantitative method by collecting data through pre-test and post-test to measure differences in students' academic abilities before and after program implementation. The research sample consisted of 20 selected 4th grade students. In addition, data was collected through interviews with class teachers, students involved in the program, as well as classroom observations during the program. The research results showed a significant increase in student learning outcomes. Observations and interviews also indicated increased student motivation to learn as well as more effective interactions between students and teachers. The program also helps identify and implement more innovative and engaging teaching methods, which is considered an important factor in improving learning outcomes.